Chemical constituents and bioactive compounds of Goniothalumus tortilipetalus Hend (Annonaceae) - Mukhtar, M, Ropi; K, Awang,; M.R, Mustafa,; A.W, Norhanom,; Y, Ashril,; A. Hadi, A. Hamid (Malaysian Journal of Science, 2000)
A Malaysian plant. Goniothalamus tortilipetalus Hend (Annonaceae) was studied for its chemical constituents and biological activities. The stem bark of Goniothalamus tortilipetalus produced two isoquinolines namely discretamine (1) and liriodenine (2). The leaves yielded asimilobine (3), iriodenine (2) and lanuginosine (4). ln addition, non-alkaloidal aromatic compounds were also purified from the petroleum ether extract. They were 6-styryl-2-pyrone (5) and goniothalamin (6). The pharmacological study revealed that 6-styryl-2-pyrone possesses a vasorelaxant eftect on rat aorta and it is cytotoxic to KB cells (ED50 = 48.5 Âµg/ml).